Tackling the dysregulated immune-checkpoints in classical Hodgkin lymphoma: bidirectional regulations between the microenvironment and Hodgkin/Reed-Sternberg cells - Cellini, Alessandro; Scarmozzino, Federico; Angotzi, Francesco; Ruggeri, Edoardo; Dei Tos, Angelo Paolo; Trentin, Livio; Pizzi, Marco; Visentin, Andrea (Frontiers in Oncology, 2023)
Immune evasion is considered one of the modern hallmarks of cancer and is a key element in the pathogenesis of classical Hodgkin Lymphoma (cHL). This haematological cancer achieves effective avoidance of the host’s immune system by overexpressing the PD-L1 and PD-L2 proteins on the surface of the neoplastic cells. Subversion of the PD-1/PD-L axis, however, is not the sole contributor to immune evasion in cHL, as the microenvironment nurtured by the Hodgkin/Reed-Sternberg cells is a major player in the creation of a biological niche that sustains their survival and hinders immune recognition. In this review, we will discuss the physiology of the PD-1/PD-L axis and how cHL is able to exploit a plethora of different molecular mechanisms to build an immunosuppressive microenvironment and achieve optimal immune evasion. We will then discuss the success obtained by checkpoint inhibitors (CPI) in treating cHL, both as single agents and as part of combination strategies, analyzing the rationale for their combination with traditional chemotherapeutic compounds and the proposed mechanisms of resistance to CPI immunotherapy.